Epigenetic Mechanisms Involved in HCV-Induced Hepatocellular Carcinoma (HCC) - Zhao, Pin; Malik, Samiullah; Xing, Shaojun (Frontiers in Oncology, 2021)
Hepatitis C virus (HCV) infection largely causes hepatocellular carcinoma (HCC) worldwide with 3-4 million newly infected cases diagnosed each year. It is urgent to explore its underlying molecular mechanisms for therapeutic treatment and biomarker discovery. However, the mechanisms of carcinogenesis in chronic HCV infection have not been still fully understood, which involve a complex epigenetic regulation and cellular signaling pathways. Here, we summarize 18 specific gene targets and different signaling pathways involved in recent findings. With these epigenetic alterations requiring histone modifications and DNA hyper or hypo-methylation of these specific genes, the dysregulation of gene expression is also associated with different signaling pathways for the HCV life cycle and HCC. These findings provide a novel insight into a correlation between HCV infection and HCC tumorigenesis, as well as potentially preventable approaches.